2022
DOI: 10.1002/aenm.202102116
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling a Three Phase Mixed Heterojunction via Phase‐Selective Anchoring of Polymer for Efficient Photocatalysis

Abstract: because solar energy is freely available and hydrogen fuel is clean with high gravimetric energy density. For practical applications, it is very important to develop a low-cost water-splitting photocatalyst with an ≈10% solar-to-hydrogen energy conversion. [4] Nearly half of the energy in the sunlight that reaches Earth's surface comes from visible light photons (400-700 nm); therefore, it is important to develop a visible light active photocatalyst for efficient solar-to-fuel conversion. [5] Most of the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…As revealed in Figure 5c and Figure S36a surface, which was quickly reduced or diminished under the applied reduction potential, additionally confirming the wellmaintained structure under the NitRR condition (Figure 5d and Figure S36b). 36,37 Although pure Ni(OH) 2 exhibits a poor NitRR performance (low NH 3 FE and yield rate), the generation of a small amount of in situ formed Ni(OH) 2 under the alkaline media could also enhance the water adsorption and dissociation step, thus supplying necessary protons to the electrophilic single-atom site and indirectly improving the NitRR performance of the Gd SA -D-NiO 400 (Figure S37). 28,38 More importantly, post stability characterizations (XRD, HAADF-STEM, EDS, XPS, and FT-EXAFS) revealed that the structure and electrophilic nature of the Gd SA sites were well maintained after the cycling test, further attesting to their superior chemical stability (Figure S38).…”
Section: Resultsmentioning
confidence: 99%
“…As revealed in Figure 5c and Figure S36a surface, which was quickly reduced or diminished under the applied reduction potential, additionally confirming the wellmaintained structure under the NitRR condition (Figure 5d and Figure S36b). 36,37 Although pure Ni(OH) 2 exhibits a poor NitRR performance (low NH 3 FE and yield rate), the generation of a small amount of in situ formed Ni(OH) 2 under the alkaline media could also enhance the water adsorption and dissociation step, thus supplying necessary protons to the electrophilic single-atom site and indirectly improving the NitRR performance of the Gd SA -D-NiO 400 (Figure S37). 28,38 More importantly, post stability characterizations (XRD, HAADF-STEM, EDS, XPS, and FT-EXAFS) revealed that the structure and electrophilic nature of the Gd SA sites were well maintained after the cycling test, further attesting to their superior chemical stability (Figure S38).…”
Section: Resultsmentioning
confidence: 99%
“…It is easy to recombine, so that the quantum efficiency becomes very low, thereby affecting the photocatalytic efficiency. In order to improve the photocatalytic activity of TiO 2 , a lot of studies have been carried out on the modification of TiO 2 [109–114] . This section briefly introduces metal doping, non‐metal element modification, recombination of TiO 2 with other semiconductors, and multi‐component co‐doping.…”
Section: Modification Principle and Methods Of Tio2‐based Nanomaterialsmentioning
confidence: 99%
“…In order to improve the photocatalytic activity of TiO 2 , a lot of studies have been carried out on the modification of TiO 2 . [109][110][111][112][113][114] This section briefly introduces metal doping, non-metal element modification, recombination of TiO 2 with other semiconductors, and multicomponent co-doping.…”
Section: Modification Principle and Methods Of Tio 2 -Based Nanomater...mentioning
confidence: 99%
“…With the development of sustainable clean‐energy sources, artificial photosynthesis conversion has become promising for transforming solar energy into storable fuel. [ 123 ] Many IIC materials have been studied because of their large molar absorption coefficient from the conjugated structure and strong ion‐involved interactions with reactants. As for type I, the zwitterionic resonance structure could induce the local polarization and separate the charge carriers effectively.…”
Section: Applicationsmentioning
confidence: 99%